Asymmetries in the trans-atlantic monetary policy relationship : does the ECB follow the Fed? - Ansgar Belke; Daniel Gros (Center for Economic Studies and ifo Institute (CESifo), 2005)
The belief that the ECB follows the US Federal Reserve in setting its policy is so entrenched with market participants and commentators that the search for empirical support would seem to be a trivial task. However, this is not the case. We find that the ECB is indeed often influenced by the Fed, but the reverse is true at least as often if one considers longer sample periods. There is empirically little support for the proposition that there has been for a long time a systematic asymmetric leader-follower relationship between the ECB and the Fed. Only after September 2001 is there more evidence of such an asymmetry. We also find a clear-cut structural break between the pre-EMU and the EMU period in terms of the relationship between short term interest rates on both sides of the Atlantic.
Keywords: F41; E58; E52; 330; co-movement of interest rates; European Central Bank; Federal Reserve; monetary policy; policy coordination; Geldpolitik; Zinspolitik; Internationale wirtschaftspolitische Koordination; EU-Staaten; Vereinigte Staaten